Investigating the Perceptions and Characteristics of the Undergraduate and Graduate Students on Cyber-Mobbullyism in Higher Education - Mitsunori Misawa (Adult Education Research Conference, 2018)
This presentation will focus on the examination of undergraduate and graduate students’ perceptions and characteristics of cyber-mobbullying in higher education. Practical implications for adult educators will also be provided.
Keywords: cyber-mobbullyism; adult and higher education; students; survey research; bullying